A novel full scale laboratory for yacht engineering research. (1st August 2015) - Fossati, F.; Bayati, I.; Orlandini, F.; Muggiasca, S.; Vandone, A.; Mainetti, G.; Sala, R.; Bertorello, C.; Begovic, E.
Abstract: This paper presents an overview of the Lecco Innovation Hub project and in particular to the Sailing Yacht Lab project a 10 m length sailing yacht which aims to be a full scale measurement device in the sailing yacht research field. A description of scientific framework, measurement capabilities as well as of the principal design, building process, project management and commissioning is provided with some examples of preliminary collected data obtained during the first sea trials. Finally an overview of the ongoing project tasks and future project developments is provided including potential research and knowledge achievements for sailing yacht research field. Highlights: Overview of the Lecco Innovation Hub – Sailing Yacht Lab project. Description of scientific frame, measurement capabilities. Examples of preliminary data collected. Overview of the ongoing project tasks and future project developments. Discussion on the potential research and knowledge achievements.